Asymmetric behaviours of brain oscillations in the human hippocampus during spatial navigation tasks. Issue 3 (10th February 2016) - Kang, Joong Koo; Lee, Eun Mi; Kim, Dajeong; Hye Lee, Seong; Kim, Taekyung; Park, Young Min; Park, Jinsick; Kim, Sun I.; Kim, In Young; Jang, Dong Pyo
Abstract : Hippocampal-dependent memory functions may be lateralized to the right hippocampus during spatial navigation. However, direct electrophysiological evidence supporting these findings in the bilateral hippocampi during spatial navigation has not been well documented in humans. We studied changes in brain oscillations between the dominant and the nondominant hippocampi during encoding periods of environmental novelty using spatial navigation tasks. Results showed that brain oscillations during the encoding period of spatial navigation increased significantly in the nondominant hippocampus compared with the dominant hippocampus. These findings provide direct electrophysiological evidence that the nondominant hippocampus plays a predominant role in spatial navigation.